Pertanggungjawaban Pidana dan Sanksi Administrasi bagi Apoteker yang Mengedarkan Obat Keras Tanpa Resep Dokter Secara Online - Yeni Vitrianingsih Arum Khofifah Kurniawati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the practice of pharmacists distributing prescription drugs without a doctor's prescription through digital platforms. This research uses a normative juridical method by examining provisions in the Pharmacy Law and the Health Law as the basis for analysis. The results indicate that this practice has the potential to violate applicable legal provisions, particularly regarding standards for drug distribution and use. This action directly reflects a failure to meet standards for drug safety and appropriate use. From an administrative perspective, pharmacists can be subject to sanctions ranging from warnings to restrictions or revocation of their Pharmacist Practice License (SIPA). Furthermore, this problem is not only related to legal aspects but also indicates a decline in professional ethics and low awareness of the use of digital technology in the health sector. Therefore, policy synchronization and strengthened coordination between the Ministry of Health, the BPOM (National Agency of Drug and Food Control), and the Ministry of Communication and Informatics to ensure consumer protection. Strategic efforts that can be implemented include operational integration between the Electronic Pharmacy System Organizer (PSEF) system and the BPOM, periodic digital audits by the Health Office, and the application of methods to assess pharmacist compliance. Furthermore, increasing digital literacy and education for the public is an important step in supporting the safe and rational use of drugs in the digital era.